An assessment of banking sector performance in Indonesia - Nurullah, Asfeni; Gozali, Efva Octavina Donata; Hamzah, Ruth Samantha; Bakti, Herdan; Khasman, Raihandito; Maharani, Maura Aviona (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study examines the effect of dividend pay-out ratio (DPR), total assets, and asset growth on banking company performance, measured by return on assets (ROA) and net profit margin (NPM). Research methodology: Using purposive sampling, we obtained 67 banking companies as samples, comprising 33 unlisted firms and 34 listed firms on the IDX. This study observed a 9-year period from 2011 to 2019; thus, the total sample comprises 603 firm-year observations. Linear regression analysis was used to analyze the data. Results: The results show that DPR and total assets, namely ROA and NPM, have a significant effect on the performance of banking companies. Asset growth had a significant effect on NPM. However, asset growth has no significant effect on ROA. Limitations: We acknowledge that we solely used a banking corporation in Indonesia. Nevertheless, to demonstrate the bigger picture of the study findings in terms of banking performance, further studies should employ banking corporations in all emerging countries. Contribution: The results enrich the theoretical knowledge about these factors in financial performance, particularly in the Indonesian banking industry. Practical Implications: Corporation management might consider this finding when making decisions regarding dividend ratios, asset size, and asset growth. Further, management needs to pay attention to these factors when planning business strategies and making decisions to achieve higher financial performance. Novelty: To the best of our knowledge, this is the first study to examine the relationship between DPR, total assets, and asset growth to performance that employs samples of the banking industry from listed and unlisted companies on the IDX.